High-spatial resolution measurements with a GaAs:Cr sensor using the charge integrating MÖNCH detector with a pixel pitch of 25 μm. (1st April 2022) - Chiriotti, S.; Barten, R.; Bergamaschi, A.; Brückner, M.; Carulla, M.; Chsherbakov, I.; Dinapoli, R.; Fröjdh, E.; Greiffenberg, D.; Hasanaj, S.; Hinger, V.; King, T.; et al.
Abstract: The aim of this project is to determine the imaging capabilities of a 25 μm pixel pitch GaAs:Cr sensor of 500 μm thickness bump-bonded to the charge integrating MÖNCH 03 readout chip (also called GaAs-MÖNCH assembly) and to assess the possibility to improve the spatial resolution by applying a position interpolation algorithm developed at PSI. Measurements were performed at the TOMCAT beamline of the Swiss Light Source (SLS) using photon beams in the energy range of 10–30 keV. The imaging experiments indicate the possibility to enhance the spatial resolution of the detector beyond its actual physical pixel pitch. We have quantified the spatial resolution of a GaAs-MÖNCH assembly by means of the modulation transfer function (MTF), achieving 10 μm at 10 keV and 12 μm at 20 keV photon energies. By applying a modified interpolation algorithm, a spatial resolution of ∼5 μm was obtained for 16 keV when binning to 2.5 μm virtual pixels, while with the silicon-MÖNCH assembly, we achieved a spatial resolution of 3.5 μm, which serves as gold standard. The results are promising because they open new possibilities to perform imaging measurements using the GaAs-MÖNCH assembly at photon energies above 15 keV, where silicon sensors suffer from a diminishing quantum efficiency.